Unconscious Dissemblance: The Place of Irony in Psychoanalytic Thought - Walsh, Julie (Pivot: A Journal of Interdisciplinary Studies and Thought, 2011)
<span style="font-size: 12.0pt; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: ";Times New Roman";; letter-spacing: .1pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">In this paper I work from the premise that the Freudian dialectic of honesty and deception challenges the order of ‘authentic’ expression by positing unconscious dissemblance as primary to the structure of the mind. The device that facilitates my reading is irony. I explore the place of irony within psychoanalytic discourse and formulate a distinction between a reading of irony as conscious application (a technique for living), and a reading of irony as unconscious mechanism (the dissembling unconscious).